Use of implementation science models, theories, and frameworks in pediatric rehabilitation: Protocol for a scoping review - Bayley Levy; Dorothy Luong; Shauna Kingsnorth; Iveta Lewis; Gillian King; Evdokia Anagnostou; Nadia Lise Tanel; Brayden Levillard; Gillian Molzon; Himanshi Elugoti; Mariam Jawad; Sarah Munce (PLoS ONE, 2026)
Introduction Implementation science frameworks – including process models, determinant frameworks, classic theories, implementation theories, and evaluation frameworks – are increasingly used to guide the translation of evidence-based interventions into practice. In paediatric rehabilitation, where interventions are complex and often require multidisciplinary collaboration, these frameworks can support systematic and context-sensitive implementation. However, the extent to which these frameworks have been used has not been comprehensively reviewed. Objective Determine the extent, nature, and specific contexts of the existing literature on the use of implementation science models, theories, and/or frameworks (MTFs) in paediatric rehabilitation. Methods This scoping review will follow the Joanna Briggs Institute (JBI) methodological guidance for scoping reviews. A comprehensive search strategy will be developed with a health sciences librarian and applied across multiple electronic databases: MEDLINE (Ovid), Embase, CINAHL, PsycINFO, ACM Digital Library, Web of Science, the Cochrane Central Register of Controlled Trials, PEDro, and RehabData. We will search English language articles published since 2006. Studies will be included if they report on the application of implementation science MTFs in the context of paediatric rehabilitation. Screening of titles and abstracts and full texts will be performed independently and in duplicate using Covidence. Discrepancies will be resolved through discussion or a third reviewer. Data will be extracted using a standardized form. Quantitative data will be summarized using numerical counts. Qualitative data will be analyzed using content analyses. Results This review will report on the use of implementation science MTFs in paediatric rehabilitation, identifying trends on the specific types applied, highlight gaps and/or underutilization across domains or developmental stages, and potentially uncover emerging frameworks. Finally, the results may inform the development of future implementation strategies and capacity-building initiatives within the field.